Risk of Invasive Escherichia coli (E. coli) Disease After Elective Urologic Procedures Among Older Adults in the United States - Maureen P. Neary; Maryaline Catillon; Nina Ahmad; Marjolaine Gauthier-Loiselle; Jeroen Geurtsen; Alice Qu; Corinne Willame; Martin Cloutier; Antoine C. El Khoury; Elie Saade (Infectious Diseases and Therapy)
Abstract Introduction Little is known about the risk of invasive E. coli disease (IED) after elective urologic procedures. We estimated the risk of IED after selected urologic procedures in patients with or without antibiotic prophylaxis, and in controls with no urologic or other surgical procedures. Methods The Komodo Research Database (01/01/2021–06/30/2023) was used to identify patients ≥ 60 years old with selected urological procedures (index: first urologic procedure date) and randomly selected controls without surgical procedures (index: random date). Patients with urologic procedures were classified into two cohorts based on whether or not they received antibiotic prophylaxis within 14 days prior to and on index date. Entropy balancing adjusted for differences between groups in selected patient characteristics over 6 months pre-index (baseline). IED rates within 30 days post-index were assessed based on recorded diagnosis of E. coli sepsis (ICD-10-CM: A41.51); odds ratios (OR) were estimated using weighted logistic regression. Sensitivity analyses within 90 days and using broader claims-based algorithm for IED were performed. Results Overall, 141,418 patients had urologic procedures with antibiotic prophylaxis, 200,062 had them without antibiotic prophylaxis, and 424,254 had no procedures. Within 30 days post-index, IED rates were 0.48% and 0.72% among patients with or without antibiotic prophylaxis, respectively, vs. 0.02% among those without any procedures. Among patients with urologic procedures,  > 70% of IED events occurred within 30 days. Patients who had urologic procedures without prophylaxis had a higher risk of developing IED than those with prophylaxis (OR = 1.50, 95% confidence interval [CI: 1.37–1.65]), while patients without any procedures had a lower risk than those with urologic procedures and prophylaxis (OR = 0.04, 95% CI [0.03–0.05]). Similar results were obtained in sensitivity analyses. Conclusions Urologic procedures were associated with an increased IED risk even with antibiotic prophylaxis. Results suggest an unmet need for additional preventative measures to reduce the burden of IED after urologic procedures.